The evaluation of active labour market policies : measures, public private partnerships and benchmarking - Koning, J. de (Jaap) (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2007)
This book argues that active labour market policies are necessary to improve the position of the unemployed but have so far performed relatively poorly.
Includes bibliographical references and index.
rua 04/05/15
Loans
Keywords: Manpower policy -- Europe; Labor market -- Europe